Analysis on bonding wires of Au-Coated Ag alloy for IBGA automotive application - Palagud, Jose; Lim, T.S.; Jasmee, Solehah; Masdzarif, Nur Diana Izzani; Wang, S.W.; Hoo, K.I.; Omar, Ghazali (2023)
In semiconductor packaging, wire bonds have been an important interconnect, and over the years, the use of other wire bonds other than Gold (Au) such as Silver (Ag) and Copper (Cu) wires has started, driven by the lower cost offered. Unfortunately, these bonding wires cannot surpass the superior properties of Au wire bonds. Thus, Au coated Ag wire bond was seen as one of the emergences in wire bond technology which can provide similar properties with Au wires but in a lower cost. This study will provide a significant contribution to the use of Ag alloy in semiconductor industries as there are still limited studies of Au-coated Ag as bonding wires. The results show that the free air-ball (FAB) can be perfectly formed at higher Electronic Flame Off (EFO) current but have inconsistency when lower in EFO current setting. A higher EFO currents setting with lower EFO time is much preferred combination as predicted by design of experiment (DOE) CZ. The formed FAB also shows great bondability performance of Au-coated Ag with the inter-metallic compound (IMC) growth for the FAB is greater than 60%, which shows the positive effect of good diffusion and bonding. Second settings validation also showed that Au coated Ag alloy wire have positive response during small scale validation. Loop formation is also consistent and there were no wire related failures observe during the validation run.